Modelers of students’ entrepreneurial intention during the COVID-19 pandemic and post-pandemic times: The role of entrepreneurial university environment - Trif, Simona Mihaela; Noja, Gratiela Georgiana; Cristea, Mirela; Enache, Cosmin; Didraga, Otniel (Frontiers in Psychology, 2022)
This paper examines the shaping factors, drivers, and impact credentials of students’ entrepreneurial intention during the COVID-19 pandemic. The proposed framework addresses the antecedents of entrepreneurial intention among students in Romania, focusing on three focal constructs, namely, risk-taking, proactiveness, and innovativeness, with a keen focus on the mediation effect of the entrepreneurial university environment. The study used self-reported data collected through an online questionnaire during November 2020–February 2021 from a sample of 1,411 students in western Romania. The methodology relies on two modern techniques of modeling cross-sectional data, namely, structural equation modeling (SEM) and Gaussian graphical models (GGMs). The main results highlight that the three constructs positively relate to students’ entrepreneurial intention in a comprehensive framework where the entrepreneurial university environment drives innovativeness. The paper brings forward, in an innovative way, that entrepreneurship education and training at the university level enhance students’ entrepreneurial intentions as it fosters the attainment of advanced knowledge and skills. The results are well associated with the start-up process as prerequisites for successful entrepreneurship engagement of youth in a globalized digital economy, particularly during this challenging pandemic outbreak, but also post-pandemic times. This research sheds new light on the essential role played by higher education institutions in providing advanced knowledge and necessary skills matched with the labor market needs, thus enhancing students’ innovativeness and their entrepreneurial intentions.